2005
DOI: 10.1029/2005gl022399
|View full text |Cite
|
Sign up to set email alerts
|

Observations of stratospheric warmings and mesospheric coolings by the TIMED SABER instrument

Abstract: [1] We used temperature data from the Sounding of the Atmosphere with Broadband Emission Radiometry (SABER) on the the NASA TIMED satellite to quantify the connection between temperatures in the stratosphere and in the mesosphere and lower thermosphere. Specifically, we studied three winter periods where stratospheric temperatures were dynamically disturbed:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 18 publications
12
83
2
Order By: Relevance
“…1 was found by Siskind et al (2005), who used Sounding of the Atmosphere with Broadband Emission Radiometry (SABER) satellite temperature observations validated with OH airglow temperatures to conclude that mesospheric temperatures between 0.7 and 0.01 hPa showed a significant anticorrelation with stratospheric temperatures. Above 0.01 hPa this correlation was seen to break down, which is in accordance with the lack of cooling observed between ∼ 86 and ∼ 90 km over Trondheim.…”
Section: Discussionmentioning
confidence: 99%
“…1 was found by Siskind et al (2005), who used Sounding of the Atmosphere with Broadband Emission Radiometry (SABER) satellite temperature observations validated with OH airglow temperatures to conclude that mesospheric temperatures between 0.7 and 0.01 hPa showed a significant anticorrelation with stratospheric temperatures. Above 0.01 hPa this correlation was seen to break down, which is in accordance with the lack of cooling observed between ∼ 86 and ∼ 90 km over Trondheim.…”
Section: Discussionmentioning
confidence: 99%
“…The observations also indicate that the perturbations in the stratospheric zonal wind affect gravity wave propagation into the MLT. Siskind et al (2005) found from SABER temperature observations that the mesospheric cooling associated with the stratospheric warming events was confined to the levels below about 85-95 km.…”
Section: Mlt Variations Due To Active Winter Dynamicsmentioning
confidence: 99%
“…Also the mesosphere (e.g., Labitzke, 1972;Jacobi et al, 2003;Siskind et al, 2005Siskind et al, , 2010Hoffmann et al, 2007;Yamashita et al, 2013;Zülicke and Becker, 2013), and even the thermosphere/ionosphere are affected (e.g., Goncharenko and Zhang, 2008;Fuller-Rowell et al, 2010;Yigit et al, 2014). The selective filtering of gravity waves by the anomalous winds during (major) SSWs is an important mechanism in these vertical influences.…”
Section: Effects Of Gravity Waves During Sswsmentioning
confidence: 99%
“…SSWs are associated with mesospheric coolings (e.g., Labitzke, 1972;Siskind et al, 2005;Hoffmann et al, 2007) that are likely driven by dissipation of eastward propagating gravity waves (e.g., Holton, 1983;Miller et al, 2013). As a consequence, the zonal wind in the mesosphere/lower thermosphere (MLT), that is usually directed westward during winter, can change its sign to eastward (e.g., Holton, 1983).…”
Section: Effects Of Gravity Waves During Sswsmentioning
confidence: 99%